2017
DOI: 10.2147/ndt.s137183
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and risk factors of young male schizophrenics with non-alcoholic fatty liver disease

Abstract: ObjectiveIn this study, we compared the prevalence rate of non-alcoholic fatty liver disease (NAFLD) between young males with schizophrenia and the general young males as the control group, and we also investigated the risk factors of NAFLD in young males with schizophrenia.Materials and methodsThis is a large cross-sectional study consisting of the study group and parallel control group. The study group comprises 202 cases of young males with schizophrenia recruited from Liaoning province Demobilized Soldiers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Yan and colleagues, in a large cross-sectional study comparing young males with schizophrenia with general young males, found a significantly higher prevalence of NAFLD of up to 49.5% in the study group compared to 20.1% in the control group. They found the factors most correlated with NAFLD were triglyceride levels, BMI, medication combinations, drug dosage, and negative factor scores on the PANSS [ 37 ].…”
Section: Epidemiology and Natural Historymentioning
confidence: 99%
“…Yan and colleagues, in a large cross-sectional study comparing young males with schizophrenia with general young males, found a significantly higher prevalence of NAFLD of up to 49.5% in the study group compared to 20.1% in the control group. They found the factors most correlated with NAFLD were triglyceride levels, BMI, medication combinations, drug dosage, and negative factor scores on the PANSS [ 37 ].…”
Section: Epidemiology and Natural Historymentioning
confidence: 99%
“…The study in Spain used fatty liver index to determine the presence of liver steatosis, which predicted fatty liver disease based on body mass index (BMI), waist circumference, and triglyceride and gamma-glutamyltransferase levels [ 30 ]. Yan et al conducted a cross-sectional study in Liaoning, China, showing that the prevalence of NAFLD was 49.5% in 202 young males with schizophrenia [ 21 ]. In the present study, male schizophrenia inpatients aged 50–59 years had the highest NAFLD prevalence of 29.78%, which was still lower than that in the Liaoning study.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to western population, the lifestyle and genetic factors causing NAFLD were different in Chinese population [ 20 ]. A recent cross-sectional study found that the prevalence of NAFLD was 49.5% in young males with schizophrenia, [ 21 ] which highlighted the need for more attention to fatty liver disease in schizophrenia patients. However, this above study only included 202 cases of young male schizophrenia patients, without female and elder participants [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies have been performed in other severe psychiatric disorders, mainly in schizophrenia. In a recent cross‐sectional study including 202 young males with schizophrenia, Yan et al observed a prevalence of NAFLD of 49.5% 24 . Using the fatty liver index in a sample of 205 drug‐naïve individuals with first episode of schizophrenia, Morlán‐Coarasa et al showed a prevalence of NAFLD of 7% 25 .…”
Section: Discussionmentioning
confidence: 99%